Mixed phase silicon thin films grown at high rate using 60 MHz assisted VHF-PECVD technique. (December 2015) - Juneja, Sucheta; Sudhakar, S.; Gope, Jhuma; Kumar, Sushil
Abstract: Mixed phase amorphous and nanocrystalline silicon (a-Si:H and nc-Si:H) thin films were deposited by VHF-PECVD (60 MHz) using Argon (Ar) as the diluent of silane. These amorphous and crystalline silicon thin films were deposited by varying the argon dilution ( f Ar ) from 10–97.5% while keeping other process parameters constant. The effects of argon dilution on deposition rate, structural and optical properties of micro/nanocrystalline silicon thin films are studied. It has been observed that the films deposited from f Ar 10–70% showed the deposition rate >20 Å/s with the highest deposition rate achieved of 25 Å/s. Structural characterization has been performed by micro-Raman analysis and Atomic force microscopy. Raman shift towards higher wave number (515 cm −1 ) with increase of f Ar indicates variation in crystallinity of silicon films. HRTEM studies revealed the distribution of grain size and the degree of crystallinity. Optical absorption spectroscopy confirmed the increase in band gap of the materials from 1.5 to 2.1 eV.